Long-case Observation in Undergraduate Medical Education. A case study - Clive Weston (2012)
Clerking patients is a fundamental clinical skill acquired by medical students. Through this dialogue with patients clinicians understand both the pathophysiology of symptoms and the person experiencing them. While students receive instruction on individual components of clerking in clinical skills laboratories, it is rare for students to be observed clerking a patient, in a clinical setting, from beginning to end. Within Swansea University’s Graduate-Entry Medicine Programme, students participate in Long-Case Observations – a senior clinical teacher witnesses an entire interaction between student and patient, gives immediate feedback, and later written feedback. The student reflects on their performance by listing learning points.Using Case Study Research to explore the educational value of long-case observation, I performed semi-structured interviews with three second-year medical students. Transcripts were analysed using a hybrid approach of inductive and deductive coding and theme development. Other data were examined for supporting and contradictory evidence.The students found long-case observation educationally worthwhile. They used the experience to gauge their progress on the course; to prepare for professional practice; to form educational relationships with clinical teachers; and to spend time interacting (and considering future interactions) with patients. Its inclusion in the curriculum served to counter the influence of exam-driven learning, to emphasise the importance of student-patient and doctor-patient interactions and to demonstrate that clinical teachers valued undergraduate education and cared for the students.Long-case observation could be used to endorse a humane approach to patients, and reverse some of the erosive qualities of the hidden curriculum.